Influence of distracter on perceived stimulus length and angle size - Bertulis, Algis; Bulatov, Aleksandr; Bielevičius, Arūnas (Psichologija, 2008)
This study describes experiments in which subjects adjusted the spatial positions of spots in three different kinds of basic stimuli in order to best perceive a required spatial property: 1) vernier alignment in a three-spot line arrangement, 2) orthogonality in a right-angled triangle constructed of three spots, or 3) length equality in a Brentano type figure. The magnitudes of the perceptual errors were measured as functions of the distance between the spots and flanking objects placed in close proximity to the spot stimuli. Quantitative characteristics of the strengths of the different illusions were obtained with the flanking objects placed at varying extents of spatial separation. The data were interpreted in terms of centroid biases caused by local integration processes. An appropriate analytical description of the experimental data was proposed, and good correspondence between it and the data was obtained. The calculated spatial parameters of the local lateral integration showed a linear dependence on the stimulus size.
Keywords: illusions of alignment, right angle and linear extent; contextual flanks; local integration; centroid bias